Turn it up! : a pitch-perfect history of music that rocked the world - Levy, Joel, 1971- (National Geographic kids., 2019)
Infographic presentation of musical history from the earliest known relics and documents, to movements in classical, opera, Latin, country, jazz, and ragtime, to modern blues, rock, K-pop, and hip-hop styles. Features brief artist profiles, information on musical instruments, fact boxes, a timeline, a glossary, an index, and resources for further research.